Adherence to Pulmonary Rehabilitation in COPD: A Qualitative Exploration of Patient Perspectives on Barriers and Facilitators - Oates, Gabriela R. (J Cardiopulm Rehabil Prev, 2019)
PURPOSE: Adherence to pulmonary rehabilitation (PR) is low. This qualitative study used the PRECEDE model to identify predisposing (intrapersonal), reinforcing (interpersonal), and enabling (structural) factors acting as barriers or facilitators of adherence to PR, and elicit recommendations for solutions from COPD patients. METHODS: Focus groups with COPD patients who had attended PR in the past year were conducted. Sessions were recorded, transcribed verbatim, and coded independently by two coders, who then jointly decided on the final coding scheme. Data were summarized across groups, and analysis used a thematic approach with constant comparative method to generate categories. RESULTS: Five focus groups with 24 participants were conducted. Participants, mean age 62 yr, were 54% male, 67% Black. More than half had annual income less than $20,000, 17% were current smokers, and 54% had low adherence (less than 35% of prescribed PR sessions). The most prominent barriers included physical ailments and lack of motivation (intrapersonal), no support system (interpersonal), transportation difficulties, and financial burden (structural). The most prominent facilitators included health improvement, personal determination (intrapersonal), support from peers, family, and friends (interpersonal), and program features such as friendly staff and educational component of sessions (structural). Proposed solutions included incentives to maintain motivation, tobacco cessation support (intrapersonal), educating the entire family (interpersonal), transportation assistance, flexible program scheduling, and financial assistance (structural). CONCLUSION: Health limitations, social support, transportation and financial difficulties, and program features impact patients’ ability to attend PR. Interventions addressing these interpersonal, intrapersonal, and structural barriers are needed to facilitate adherence to PR.